Signal-theoretic characterization of waveguide mesh geometries for models of two-dimensional wave propagation in elastic media. - Fontana, F.
Waveguide meshes are efficient and versatile models of wave propagation along a multidimensional ideal medium. The choice of the mesh geometry affects both the computational cost and the accuracy of simulations. In this paper, we focus on two-dimensional (2-D) geometries and use multidimensional sampling theory to compare the square, triangular, and hexagonal meshes in terms of sampling efficiency and dispersion error under conditions of critical sampling. The analysis shows that the triangular geometry exhibits the most desirable tradeoff between accuracy and computational cost
Keywords: 2D geometries; Accuracy; Computational cost; Critical sampling; Dispersion error; Elastic media; Hexagonal meshes; Models; Multidimensional ideal medium; Multidimensional sampling theory; Sampling efficiency; Signal-theoretic characterization; Simulations; Square meshes; Triangular meshes; Two-dimensional wave propagation; Waveguide mesh geometries